PANEN SAHAM BURSA INDONESIA MELALUI EDUKASI PENGGUNAAN ANALISA SAHAM PADA ARISAN BANK MANDIRI - Maryanti Maryanti; Leli Sumarni (LPPM Universitas Andalas, 2023)
The wife's routine from her husband who works at Bank Mandiri, who has free time after completing daily household chores, provides an opportunity for the wife to increase family income. In fact, it is not uncommon to become the husband's biggest income who works at an independent bank through stock harvesting activities. The opportunity to harvest shares is provided in the form of two online class meetings held in the arisan class of the Bank Mandiri Family Wives Association (IIKBM). This activity was attended by 35 members of the IIKBM arisan. The purpose of this activity is to not only be able to fill the wife's spare time at home, but also to increase the family's income. The method used in this activity uses the lecture, discussion, consultation and evaluation methods. This activity introduces knowledge about shares circulating on the Indonesia Stock Exchange, daily 'cash' opportunities, and investment opportunities in the long-term capital market using lecture and discussion methods (2 days). The consultation and practice method was carried out for 2 days to start the practice of harvesting shares on the stock exchange and creating a whatsappgroup to facilitate the results of the practice. The evaluation method was carried out for 2 days which contained an evaluation of the problems and solutions obtained from the whatsappsgroup. The result of this activity is that IIKBM arisan members gain knowledge about harvesting shares and investing in the profitable capital market as additional family income without the need to leave the house. The evaluation of the results of this activity is to provide a response to the responses, messages, and recommendations for 'cuan' ​​shares discussed in the whatsapp group.